Risk assessment of oil drilling rig welded pipe based on structural integrity and life estimation. (May 2020) - Zaidi, Radzeya; Sedmak, Aleksandar; Kirin, Snezana; Grbovic, Aleksandar; Li, Wei; Lazic Vulicevic, Ljubica; Sarkocevic, Zivce
Highlights: Simple engineering approach has been used as efficient method to assess risk by fracture mechanics. The simple engineering analysis tends to be over-conservative, even in relatively simple case study. More complex approach, based on FEM, is inevitable for more complex geometries. Risk based analysis is useful method to provide gap between engineers and managers. Abstract: Risk assessment procedure based on structural integrity and life estimation has been introduced and applied to oil drilling rig welded pipe. The new concept based on application of structural integrity and life estimation to assess risk level according to probability and consequence of failure was used. Oil drilling rig welded pipe integrity has been assessed by simple application of the Failure Assessment Diagramme (FAD), i.e. by using the ratio of linear elastic fracture mechanics parameter, KI, and its critical value, KIc, in relation with the ratio of applied stress and its critical value, to define the point in FAD. Probability of failure is then taken according to the position of the point in the FAD, corresponding to oil drilling rig welded pipe data. Then, the FEM has been applied to calculate more precisely the strain and stress state and to get another, less conservative, risk assessment. Oil drilling rig welded pipe life has been estimated by simple integration of the Paris law, as well as by more complex simulation of fatigue crack growth, using the extended Finite Element Method (xFEM). Probability of failure is then taken as the ratio of the number of cycles for a given crack length and the number of cycles for the critical crack length. These analyses are useful for managers to make decision about further use of damaged pipes, based on data provided by engineers. Also, the procedure introduced here for risk assessment is not limited to oil drilling rig pipes, but it is rather a general one, applicable to any component with known geometry, material properties and loading data.